Pengaruh Model Games Based Learning terhadap Keaktifan Belajar Siswa PAK Kelas XI SMA Negeri 1 Purba Kabupaten Simalungun Tahun Pembelajaran 2024/2025 - Silvia Ningsih Berutu; Maria Widiastuti; Risden Anakampun; Tahadodo Waruwu; Dame Taruli Simamora (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
The aim of this research is to determine the influence of the Games Based Learning Model on the Learning Activeness of Class The research method used is a quantitative method with a descriptive inferential type. The population was 182 students of Class Data was collected using a closed questionnaire with 14 items for variable Y and 18 items for variable 2025 is shown through: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0,308 > rtabel(α=0,05; IK=95%; n=49) = 0,281. b) a significant relationship test is obtained from the value thitung = 2,222 > ttabel = 2,021. 2) influence test: a) regression equation test, obtained the regression equation Ŷ = 42,221 (α) + 0,365 (X). b) regression coefficient of determination test (r2) = 9,5%. 3hypothesis testing using Fhitung > Ftabel=(α=0,05,dk pembilang n-1=48, dk penyebut=n-2=49-2=47) yaitu 4,938 > 1,620.Thus H0 is stating there is no influence is rejected and Ha which states there is an influence is accepted.